Efektivitas Penggunaan Fermentasi Buah Kakao (Theobroma cacao l.) Sebagai Bioherbisida Pada Gulma Patikan Kebo (Euphorbia hirta) - Rahman, Royh; Soedijo, Samharinto; Rosa, Helda Orbani (www.ulm.ac.id, 2025)
One environmentally friendly alternative for weed control is to utilize cocoa plant waste (Theobroma cacao L). Can be used as a biological herbicide. The aim of this research is the effectiveness of the long fermentation time of bioherbicides from cocoa shells and beans in controlling weeds. This research used a non-factorial Randomized Block Design (RAK), consisting of 4 treatments (K (Control), M1 (7 days), M2 (14 days), M3 (21 days) and M4 (28 days)) with as many repetitions as possible. 3 times. The results of this research show that weed growth can be suppressed with cocoa bioherbicide from observation week 1 to week 3, with the highest poisoning score being 4 (Very severe poisoning; young leaves have an abnormal shape and color until they dry out and fall off until the plant dies). Symptoms of poison caused by biorherbicides include changes in leaf color from green to pale and eventually death.